Urban Transportation Problems and Issues in Homs-Syria: Analytical Study of the Current Condition and Proposing Future Solutions - Shaheen, Saleem (International Journal of Engineering and Management Sciences, 2021)
Cities in the north middle east are known for their past and old valuable heritage, with a complex master plan of each one. Homs city is Syria is one of them, it has a history dates back to 2000B.C. with a unique formation of the city. However, the urban area of Homs has a very distinctive characteristics, but unfortunately it suffers from the transportation system operated. The congested and unorganized planning process have led the city to a complete mess and disorders, for all categories of its inhabitants. This study analysis the components of the transportation system, and identifies the greatest issues and problems the inhabitants suffer from, by locating the driving forces and the causes of these issues, and generally asses the quality of the system itself. Therefore, a holistic approach is proposed to improve the transportation system, and suggests some key plans to shift the city to a higher level of development. By locating the strength points, and detect the benefits of these strength points and exploit them. By evaluating the road network and create a new system that mitigates the negative environmental impacts (emissions, noise…) and reduce the crowded gathering of inhabitants, which caused a severe stress in their daily life. Overall, an attempt of implementing a new transportation system to contribute in the development process, and opens the possibility to develop other systems of the city in a sustainable framework.